UO2F2 particulate formation in an impinging jet gas reactor. Issue 8 (17th June 2021) - Hubbard, Joshua A.; Cheng, Meng-Dawn; Cheung, Lawrence; Kirsch, Jared R.; Richards, Jason M.; Fugate, Glenn A.
Abstract : Computational fluid dynamics (CFD), chemical kinetics, and aerosol dynamics were combined to model the formation of uranyl fluoride particles from the hydrolysis of uranium hexafluoride gas. Abstract : Computational fluid dynamics (CFD), chemical kinetics, and aerosol dynamics were combined to model the formation of uranyl fluoride particles from the hydrolysis of uranium hexafluoride gas. This chemical process has been studied for many decades, however, detailed measurements of aerosol formation have only become available in the past few years which provide a basis for model comparison. CFD simulations predicted complicated flow patterns in the impinging jet gas reactor. Aerosol formation simulations also predicted higher mass concentrations than were observed experimentally. This suggested that experimental data provided a partial representation which was subsequently enhanced by modeling and simulation.